Efektivitas Metode 3T+1M dalam Meningkatkan Hasil Belajar pada Pelajaran Qur’an Hadis - Miftahul Hida Arrohim; Sunarto Sunarto; Fathor Rahim (UIN Sunan Gunung Djati Bandung, 2022)
As one of the methods that can help smooth Qur'anic verse-based learning, the 3T+1M method has not been widely applied in Islamic Educational Institutions. In addition, the low learning outcomes of students in the Qur'an Hadith subjects are often caused by monotonous and less varied learning methods. This study aims to measure the effectiveness of the 3T + 1M method in improving student learning outcomes in the Qur'an Hadith lesson. The research method uses a quantitative approach with the type of experiment. The results obtained, the class that applies the method has an increase in value of 42% higher than the class that continues to use the conventional method. So the 3T + 1M method is proven to be effective in improving learning outcomes. The conclusion is that the Talqin, Tafahhum, Tikrar, Muraja'ah (3T+1M) learning methods are not only effective in improving students' memory skills in memorizing the Qur'an, but also effective in improving student learning outcomes in Qur'an lessons Hadith.